Historical profiles of Polycyclic Aromatic Hydrocarbons (PAHs), sources and origins in dated sediment cores from Port Klang, Straits of Malacca, Malaysia. - Sakari, Mahyar; Zakaria, Mohamad Pauzi; Mohamed, Che Abd Rahim; Lajis, Nordin; Chandru, Kuhan; Bahry, Pourya Shahpoury; Shahbazi, Azadeh; Sofia Anita, (National Institute of Informatics, 2010)

(untitled)
Polycyclic aromatic hydrocarbons and pentacyclic triterpanes (hopanes) were determined in 2 sediment cores col-lected from offshore of Klang River estuary and Old Port of Klang City, located in Straits of Malacca, Malaysia. Strait of Malacca is among the world’s busiest waterways and Port Klang is one of the busiest, premier and largest ports in the Straits. The port has been an important trading post since the colonial era of the Portuguese, Dutch and the British Straits Settlements. Old Port of Klang is heavily influenced by urban population and runoff as well as massive shipping traffic. The highest concentration of polycyclic aromatic hydrocarbons was found in Old Port Klang with PAHs from 34 to 2426 ng/g while Offshore Klang showed total PAHs concentration from 7.37 to 32.97 ng/g. Also these concentrations are significantly elevated in upper layers in both cores. Sediment core collected in Old Klang port carries mixture of petrogenic and pyrogenic signatures with methylphenan-threne to phenanthrene (MP/P) ratio range from 0.63 to 1.11while the core collected from an offshore station of the Klang river estuary revealed a highly pyrogenic signature as evidenced from the MP/P ratio of 0.22 to 0.83 indicating atmospheric transport and non-conservative behavior of the pollutant as the distance from the source increases. All sediment intervals showed PAHs concentration below the effects range-low (ER-L) sediment toxicity threshold values (total PAHs 4000 ng/g) but indicative of polluted environment (1000 ng/g). Although results from pentacyclic triterpanes in this study revealed that hopane is not a conventional molecular marker for source identification of pyrogenic sources of PAHs, but apparently showed no significant of oil spills occurred in the study area. Results from the analysis of other alkyl substitute of PAHs such as ratio of Methyl Pyrene to Pyrene (MPy/Py), parent PAHs and hopanes as well as ratios such as Fl/Py and Ph/An indicated mostly pyrogenic source orig-inated from street dust and asphalt in Klang valley including Kuala Lumpur. This indicates that the sedimentary environment around Port Klang mostly receives short and medium range transport materials via rivers and atmosphere, although heavy ship traffic and urban runoffs could easily be thought of receiving petrogenic input.